Anatomical variations of the middle Turbinate among adult Sudanese Population -A Computed Tomographic Study (Bangladesh Journal of Medical Science, 2021)
Objectives: This study aimed to determine the prevalence of the anatomical variations of themiddle turbinate among adult Sudanese population which include Concha Bullosa (CB) andParadoxical middle turbinate (PMT) and their relationship with age and sex.Methods: The studypopulation involved 29 males (47.5%) and 32 females (52.5 %) with a mean age of 37 years.Exploration was done in the radio-diagnostic department of Ribat University Teaching Hospital,Khartoum- Sudan in the period from January to September 2018. Patients were scanned on slicecollimation of 1mm thickness with a slice thickness of 4 mm. Computed Tomography (CT) scanswere retrospectively reviewed for the presence of CB and PMT coronal planes, bony windowsand reported the results in the datasheet. Statistical analysis was performed using SPSS andcompared with previous results on similar studies.Result: In the current study, the prevalence ofthe CB was 22.9%, observed bilaterally in 6 cases (9.8%), unilaterally in 8 (13.1%). PMT waspresent only in 3 cases (4.9%) all of them were unilateral.Conclusion: Computed Tomography(CT) may easily identify such uncommon anatomic variations of the osteomeatal region,determination of these variations aids in providing a better surgical orientation and avoiding orminimizing the possible complications.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.62-67